ANALISIS HUBUNGAN FERTILITAS DENGAN KEMISKINAN DI KABUPATEN BERAU - Lisa Puspita Sari (ECO-BUILD, 2025)
The purpose of this study was to determine the causality (reciprocal effect) between fertility and poverty in Berau Regency. Secondary data used were data on the number of poor people and fertility rates in Berau Regency for the period 2017-2022, which have been published by BPS Berau Regency. The analysis tools used were the classical assumption test (normality test, autocorrelation test, heteroscedasticity test), simple linear regression analysis, correlation coefficient, determination coefficient, and t-test. The conclusion of the results of this study is that there is a relationship between fertility and poverty in Berau Regency. This is proven by the results of the t-test showing a calculated t-value> t-table or 4.814> 2.132 and a significance value <probability value (0.009 <0.05). In addition, the closeness of the relationship between fertility and poverty can be seen from the correlation coefficient of 0.923 which indicates a very high or very close relationship. Likewise, the large contribution made by fertility is quite large to the poverty rate in Berau Regency, namely 85.3%.